Kinematics of nordic jumping from a standard 90-m jump and a 6.4-m indoor jump - French, J. P.; Rundell, K. W. (Medicine & Science in Sports & Exercise, 1998)
This study examined kinematic differences between a 6.4-m indoor ski jump and a 90-m outdoor jump. US Ski Team jumpers (N = 6) were filmed during two jumps from both platforms. Analyses were performed for three positions during each jump. Significant differences were identified between the two jumping forms. Angular differences in all three positions indicated that Ss were not as tucked in the small jump, take-of technique was altered, and full flight posture was not reached. Take-off velocities were markedly different for each jump. Implication. Training on a small hill requires a different jumping technique than on a large hill. The movement patterns required of jumpers is specific to the jumping task being performed.